Differences in the phototaxis of pollen and nectar foraging honey bees are related to their octopamine brain titers - Scheiner, Ricarda; Toteva, Anna; Reim, Tina; Søvik, Eirik; Barron, Andrew B. (Frontiers in Physiology, 2014)
The biogenic amine octopamine is an important neuromodulator, neurohormone and neurotransmitter in insects. We here investigate the role of octopamine signaling in honey bee phototaxis. Our results show that groups of bees differ naturally in their phototaxis. Pollen forgers display a lower light responsiveness than nectar foragers. The lower phototaxis of pollen foragers coincides with higher octopamine titers in the optic lobes but is independent of octopamine receptor gene expression. Increasing octopamine brain titers reduces responsiveness to light, while tyramine application enhances phototaxis. These findings suggest an involvement of octopamine signaling in honey bee phototaxis and possibly division of labor, which is hypothesized to be based on individual differences in sensory responsiveness.